2021
DOI: 10.1021/acsomega.1c03275
|View full text |Cite
|
Sign up to set email alerts
|

Screening of Polyphenols in Tobacco (Nicotiana tabacum) and Determination of Their Antioxidant Activity in Different Tobacco Varieties

Abstract: Tobacco (Nicotiana tabacum) is an herbaceous plant originating from South America and processed into cigarettes for consumption. Polyphenols are considered vital components of tobacco in view of their contribution to antioxidant properties. This study aimed to determine the phenolic compounds in different tobacco varieties by applying cold extraction with methanol and distilled water. The extracts were screened for phenolic compound diversity and distribution as well as their antioxidant potential in different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 61 publications
1
12
1
Order By: Relevance
“…Because phenols are highly soluble in polar solvents, they can provide higher concentrations of phenols than nonpolar solvents [ 37 ]. The amounts of phenolics found in ethanolic extracts in this study were significantly higher than previously reported by Zou et al, who reported that the methanolic extract of N. tabatum had the highest amount in terms of total phenolic content, at 24.82 ± 0.07 mg GAE/g extract [ 38 ]. However, different solvents and extraction methods were considered.…”
Section: Resultscontrasting
confidence: 76%
See 1 more Smart Citation
“…Because phenols are highly soluble in polar solvents, they can provide higher concentrations of phenols than nonpolar solvents [ 37 ]. The amounts of phenolics found in ethanolic extracts in this study were significantly higher than previously reported by Zou et al, who reported that the methanolic extract of N. tabatum had the highest amount in terms of total phenolic content, at 24.82 ± 0.07 mg GAE/g extract [ 38 ]. However, different solvents and extraction methods were considered.…”
Section: Resultscontrasting
confidence: 76%
“…Wang et al reported that ethanolic-extracted polyphenols from tobacco leaf possessed strong antioxidant activity when measured for the radical scavenging and lipid peroxidation inhibition activity [14]. Similarly, a previous investigation revealed that N. tabacum extracts exhibited strong antioxidant activities, including radical scavenging activity against DPPH and ABTS, as well as ferric reducing power, due to their polyphenols [38]. With regard to different methods to evaluate the antioxidant activity of tobacco, it was found that tobacco presented antioxidant capacity in the range of 66 to 230 μmol Trolox equivalent/g dry weight using the ORAC method [45].…”
Section: Antioxidant Activities Of N Tabacum Extractsmentioning
confidence: 99%
“…Determination of ABTS. The ABTS radicalscavenging activity of the samples was measured using the method of Peng et al 19 and Zou et al 66 The ABTS + solution was prepared by the addition of 7 mM ABTS solution and 140 mM potassium persulfate solution and incubated in the dark for 16 h. The ABTS + solution was diluted with ethanol to make an absorbance of 0.70 ± 0.02 at 734 nm. The extract (10 μL) and 290 μL of freshly prepared ABTS + solution were added to the 96-well plate and incubated at 25 °C for 6 min.…”
Section: Determination Of Dpphmentioning
confidence: 99%
“…The phenolic contents are highly associated with their antioxidant properties. Thus, several antioxidant assays were conducted to analyze the antioxidant capacity of the lotus samples. In our study, DPPH, ABTS, FRAP, and TAC were applied to estimate the antioxidant potential of different parts of the lotus.…”
Section: Resultsmentioning
confidence: 99%